Experiences of living with long COVID and of accessing healthcare services: a qualitative systematic review. Issue 1 (11th January 2022) - Macpherson, Karen; Cooper, Kay; Harbour, Jenny; Mahal, Dawn; Miller, Charis; Nairn, Moray
Abstract : Objective: To explore the experiences of people living with long COVID and how they perceive the healthcare services available to them. Design: Qualitative systematic review. Data sources: Electronic literature searches of websites, bibliographic databases and discussion forums, including PubMed LitCovid, Proquest COVID, EPPI Centre living systematic map of evidence, medRxiv, bioRxiv, Medline, Psychinfo and Web of Science Core Collection were conducted to identify qualitative literature published in English up to 13 January 2021. Inclusion criteria: Papers reporting qualitative or mixed-methods studies that focused on the experiences of long COVID and/or perceptions of accessing healthcare by people with long COVID. Title/abstract and full-text screening were conducted by two reviewers independently, with conflicts resolved by discussion or a third reviewer. Quality appraisal: Two reviewers independently appraised included studies using the qualitative CASP (Critical Appraisal Skills Programme) checklist. Conflicts were resolved by discussion or a third reviewer. Data extraction and synthesis: Thematic synthesis, involving line-by-line reading, generation of concepts, descriptive and analytical themes, was conducted by the review team with regular discussion. Results: Five studies published in 2020 met the inclusion criteria, two international surveys and three qualitative studies from the UK. Sample sizes varied from 24 (interview study) to 3762 (survey). Participants were predominantly young white females recruited from social media or online support groups. Three analytical themes were generated: (1) symptoms and self-directed management of long COVID; (2) emotional aspects of living with long COVID and (3) healthcare experiences associated with long COVID. Conclusions: People experience long COVID as a heterogeneous condition, with a variety of physical and emotional consequences. It appears that greater knowledge of long COVID is required by a number of stakeholders and that the design of emerging long COVID services or adaptation of existing services for long COVID patients should take account of patients' experiences in their design.